Laptops vs. Desktops in a Google Groups Environment: A Study on Collaborative Learning - Abrantes, Steven Lopes; Gouveia, Luis Borges (International Journal of Interactive Mobile Technologies (iJIM), 2010)
Current literature on m-learning refers to the lack of studies on real use of m-learning applications and how they can compete with current desktop counterparts. The study consists of an experiment involving one hundred and twelve students of higher education and a set of learning activities that they have to accomplish. This study has the main objective to validate if the students that use laptops or desktops are in the flow experience and which of them are more in the flow experience, when using Google Groups. The used approach is based on the flow experience introduced by [1]. It was possible to conclude that students have experienced the flow state both by students using laptops or desktops, but having the laptop students a more positive effect in the flow experience.